Regression Analysis on Publication Views and Downloads of a Philippine Journal and Its Implications to Quality Journal Management and Monitoring - Oclay, Prof Agnes D; Isla, Marvin Z; Camara, Jun S (ASEAN Multidisciplinary Research Journal, 2020)
Journal Management and Monitoring is not only about publishing articles both online and in print, but includes understanding by using available empirical data how published articles are making impact in the research community. This study, an excerpt, aimed to find a correlation between the abstract view and file view of fifty-three (53) published articles in a Philippine Journal from March 2019 to April 2020. Findings showed that abstracts are viewed more often than files, and that files are viewed more than they are downloaded. Results revealed that the two variables are statistically significantly correlated with a strong positive linear correlation, and a regression equation (y = 0.27x + 5.03) was developed to estimate future increase in the dependent variable, or File View. Recommendations on the revision of the Author Guidelines of the Philippines Journal as well as a Training on Abstract Writing were recommended.